EVALUATION OF INDICATORS OF BACTERIAL CONTAMINATION, ANTIMICROBIAL AND ANTIOXIDANT PROTECTION IN ORAL MUCOSAL HOMOGENATES OF RATS UNDER EXPERIMENTALLY INDUCED IMMUNODEFICIENCY AND DYSBIOSIS FOLLOWING A THERAPEUTIC-PROPHYLACTIC REGIMEN - Guliuk, S.A.; Shnaider, S.A.; Dienha, O.V.; Skulska, S.V.; Melnychuk, H.M.; Tashchyan, A.E.; Goncharuk, S.V. (World of Medicine and Biology, 2025)
The study was devoted to the evaluation the impact of a multi-component therapeutic-prophylactic complex on indices of bacterial contamination, antimicrobial defence, and antioxidant protection in oral mucosal homogenates of rats subjected to cyclophosphamide-induced immunodeficiency and lincomycin-associated dysbiosis. Thirty adult male Wistar rats were randomly assigned to an intact control, a combined pathology group, and a combined pathology + therapeutic-prophylactic complex group (n=10 each). Seven days after modelling the pathology, animals in the third group received the therapeutic-prophylactic complex for 30 days. Urease and lysozyme activities were quantified in mucosal homogenates, and a dysbiosis index was calculated. The therapeutic-prophylactic complex significantly reduced urease activity, restored lysozyme activity, and normalised the dysbiosis index, demonstrating pronounced antimicrobial, antioxidant, and immunostimulatory effects. These findings substantiate further exploration of the therapeutic-prophylactic complex as a promising strategy for preventing complications arising from combined immunodeficient–dysbiotic conditions.
Keywords: bacterial contamination; lysozyme; urease; immunodeficiency; dysbiosis; antioxidants; therapeutic-prophylactic complex